A comparative case study: Administrators' and students' perceptions of the Seal of Biliteracy. (1st September 2020) - Hancock, Charlotte R.; Davin, Kristin J.
Abstract: This comparative case study explores the perceived value of the Seal of Biliteracy (SoBL) between two key stakeholders, administrators and students. Drawing on interviews and focus group data from one large, urban district in Minnesota that was instrumental in assisting the state in diversifying languages awarded with the SoBL, this study investigated areas in which administrators' perceived value of the SoBL converged or diverged with linguistically diverse students' perceived value. Findings revealed convergences along the two themes of college credit and promoting multilingualism as an asset and divergences along the three themes of racial equity, proof/validation, and future opportunities. Convergences between these two groups represent the maximal zone of policy implementation whereas divergences represent areas in which work could be done to enhance the policy's potential. Implications focus on how to increase the number of linguistically diverse students earning the SoBL and highlight critical areas in need of additional research. The Challenge: Seal of Biliteracy (SoBL) implementation varies greatly and is shaped by the individuals involved. What do administrators see as the value of the SoBL? How do administrators' perceptions converge or diverge with the perceptions of linguistically diverse students? These questions illuminate how to maximize the potential of the SoBL.